Review of SCADA systems and IoT honeypots - Alquwatli, Mohammed H.; Habaebi, Mohamed Hadi; Khan, Sheroz (IEEE, 2020)
Internet of Things (IoT) is a massive technology that is being improved day by day. It connects different types of devices to the internet so that they can interchange data. The most feild that has been improved by implementing IoT’s technology is Supervisory Control and Data Acquisition (SCADA) Systems, or Industrial Control Systems (ICS). The application of these systems is to be used in controlling different elements that is connected to it (sensors, devices, and machines). However, connecting different types of devices of different physical circuitry and different communication technology, together raises various security issues that has been a place of concern for years. A famous technique that has been implemented in the field of security to further study Cyber Attacks, its causes, and effects is Honeypots. The Aim from this paper is to categorize Cyber -physical attacks and their effects, study SCADA/ICS systems’ architecture, highlight its security weaknesses, and how Cyber/Physical attacks make use of these weaknesses. Finally, a break down Honeypots and understand its implementation and effectiveness in the Field of Cyber Security.